UPAYA PENGUATAN IDEOLOGI PANCASILA MELALUI ORGANISASI EKSTRAKURIKULER PRAMUKA DI SEKOLAH MENENGAH ATAS NEGERI 1 MARGAASIH: UPAYA PENGUATAN IDEOLOGI PANCASILA MELALUI ORGANISASI EKSTRAKURIKULER PRAMUKA DI SEKOLAH MENENGAH ATAS NEGERI 1 MARGAASIH - Cahyono Cahyo Yono (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2022)
Scouting is an extracurricular organization held at all levels of education. Scouting is one of the extracurricular activities that is a place for character education, besides that Scouting also has a relationship with the ideology of Pancasila. This study aims to determine the relationship between scouts and Pancasila values. This study aims to find out how to strengthen the Pancasila ideology in Scout extra-curricular activities. So that the formulation of the problem in this research is: how is the implementation of Scout extra-curricular activities at SMA N 1 Margaasih, how is the relationship between Scout extracurricular activities and Pancasila values, what obstacles are faced in efforts to strengthen Pancasila ideology through extracurricular organizations at SMA N 1 Margaasih, what are the solutions? to face obstacles in efforts to strengthen the Pancasila ideology through Scout extracurricular organizations at SMA N 1 Margaasih. This study used a descriptive method with a qualitative approach with the research subject being Scoutmasters and students at SMA N 1 Margaasih. Data was collected by means of interviews and documentation with data analysis techniques using data reduction, data presentation, conclusion drawing and verification. The results of the study show that (1) the scout extracurricular is a mandatory extracurricular, (2) the relationship between scouts and Pancasila values ​​is contained in the dasadarma, (3) the obstacles faced are one of the students themselves, the supporting environment and the scout coach, ( 4) solutions to deal with obstacles, including the provision of scouting materials such as the history of the Indonesian nation, the use of scouting methods and increasing the ability of scout coaches.